Fahrenheit 451 : Ray Bradbury - McGiveron, Rafeeq O. (Ipswich, Massachusetts : Salem Press, a division of EBSCO Information Services ; Amenia, NY : Grey House Publishing, 2013)
"In this volume, introductory essays situate the novel in its historical and cultural context and also survey its critical reception, while subsequent chapters explore Bradbury's creation and reworking of the story, issues such as memory, love and morality, domesticity, intellectual property and censorship, and the appeal of Fahrenheit 451 in other media. Rounding out the volume is a bibliography of other important critical sources for readers seeking to study the novel and its themes further" -- provided by publisher.
About this volume / Rafeeq O. McGiveron -- On Fahrenheit 451 / Rafeeq O. McGiveron -- Biography of Ray Bradbury / Garyn G. Roberts -- Some social and cultural context on Ray Bradbury's Fahrenheit 451 / Garyn G. Roberts -- Genre, censorship, and cultural changes : critical reception of Ray Bradbury's Fahrenheit 451 from the 1950s to 2000s / Robin Anne Reid -- The phoenix and the fireman : dialogistic inversion in Ray Bradbury's Fahrenheit 451 / Joseph Michael Sommers -- From "government control of this and that" to "the whole culture's shot through" : behavior, blame, and the bomb in The Martian chronicles and Fahrenheit 451 / Rafeeq O. McGiveron -- Speaking futures : the road to Fahrenheit 451 / Jonathan R. Eller -- "Classics cut to fit"? Fahrenheit 451 and its appeal in other media / Phil Nichols -- Fahrenheit 451 and the utopic dystopia : Bradbury's vision compared to those of More, Orwell, Huxley, Wells, and Dick / Wolf Forrest -- "The house all burnt" : disintegrating domesticity in Ray Bradbury's Fahrenheit 451 / Andrea Krafft -- "Where ignorant armies clash by night" : love, war, and the women of Fahrenheit 451 / Timonthy E. Kelley -- Knowledge and masculinity : male archetypes in Fahrenheit 451 / Imola Bulgozdi -- Reading Montag as a postmodern Don Quixote / Guido Laino -- The argument about memory in Fahrenheit 451 / Anna McHugh -- If we own it, we can destroy it : Fahrenheit 451 and intellectual property / Aaron Barlow -- Bradbury, technology, and the future of reading
Includes bibliographical references and index.
Keywords: Bradbury, Ray, -- 1920-2012.; Book burning in literature; Censorship in literature; Science fiction, American -- History and criticism; Bradbury, Ray / 1920-2012 / Fahrenheit 451.; Book burning in literature; Censorship in literature; Science fiction, American -- History and criticism